Analysis of the current status and hot topics in spinal schwannoma imaging research based on bibliometrics - Abudueryimu, Abudunaibi; Shoukeer, Kutiluke; Ma, Haihong (Frontiers in Neurology, 2024)
Spinal Schwannoma Imaging Research Based on Bibliometrics 【Abstract】 Objective This study aims to explore the current hot topics and future research trends in spinal schwannoma imaging research, providing a reference for related studies and promoting the development of spinal schwannoma imaging. Methods We conducted a literature search in the Web of Science database using the search terms (((TS=(Spinal schwannoma)) AND TS=(Imaging)) OR TS=(Spinal schwannoma)) AND TS=(image) to retrieve relevant articles. The collected data, including authors, keywords, journals, countries, institutions, and references, were subjected to visual analysis using the visualization software CiteSpace 6.4.2R and VOSviewer 1.6.19. Results A total of 310 relevant articles were identified. After further screening based on time limits, inclusion, and exclusion criteria, 179 articles were included in the study, consisting of 132 original articles and 42 reviews. These articles were authored by 1034 authors from 35 countries and 324 institutions and were published in 82 different journals. The included articles cited a total of 6583 references from 1314 journals. Conclusion Although the field of spinal schwannoma imaging research is not a popular research area in the medical community, there has been an increasing international interest in this field in recent years. While China ranks high in terms of the number of published articles, there is still a gap in terms of the quality and research level compared to developed countries in Europe and America. MRI, as the gold standard for diagnosing spinal schwannomas, is expected to be a research hotspot in terms of feature analysis, enhancement characteristics, and quantitative analysis. It is also hoped that China can increase its investment in research and contribute to the field by publishing high-quality articles in the future.